Investigate the Applicability of Coating Titanium Substrate by Hydroxyapatite for Surgical Implants - Nabaa S. Radhi; Haydar H. Jamal Al-Deen; Rasha Safaa Hadi; Al-Khafaji, Zainab (International Journal of Integrated Engineering, 2024)
Pure Titanium and Titanium alloys are the materials that are utilized the most often for the production of dental implants, and hydroxyapatite is the bioactive substance that is most frequently coated on titanium implants. Ceramics are a family of biomaterials that include hydroxyapatite. This substance has structural and chemical similarities with biological apatite, the primary inorganic component of tooth and bone, and hydroxyapatite is also a ceramic. The substance is not only osteoconductive and non-toxic, but it also has bioactive properties. This research studied and manufactured a coating for surgical implants by employing hydroxyapatite (HA), a distinctive bone that grew at a medium for prosthetic human body parts. This coating was meant to boost bone development. Pulsed laser deposition (PLD) created titanium substrate HA coatings. This search employed HA compressed at 150 MPa with a particle size of 2.745 m as a coating target utilizing PLD methods with (8000, 6000, and 4000) pulses. SEM and AFM were used to describe the coating surface and determine calcium and phosphorus concentrations in the coating layer. In an in vivo study, four rabbits’ femur bones were implanted with Ti-HA-8000, Ti-HA-6000, Ti-HA-4000, and Ti. Both groups showed new bone growth surrounding the implant at three weeks. Haversian lamellae indicate mature bone growth and complete osseointegration surrounding the Ti-HA-8000 implant after six weeks, which implies that HA is biocompatible and facilitates implant-bone osseointegration.